Spontaneous remission in a patient with very late relapse of acute myeloid leukemia 17 years after allogeneic blood stem cell transplantation. (17th June 2019) - Rautenberg, Christina; Kaivers, Jennifer; Germing, Ulrich; Haas, Rainer; Schroeder, Thomas; Kobbe, Guido
Abstract: Spontaneous remission (SR) of acute myeloid leukemia (AML) represents a rare phenomenon and is usually of short duration although long‐term remissions are reported. Indeed, mechanisms underlying SR remain unclear, but it is suggested that immunactivation, e.g. caused by infections, plays an important role. Here we report on a patient who suffered from pneumonia and simultaneously experienced very late hematologic AML relapse seventeen years after allogeneic blood stem cell transplantation (allo‐BSCT). Surprisingly in parallel to recovery from pneumonia peripheral blood count which previously showed pancytopenia, had normalized and bone marrow (BM) aspiration revealed spontaneous remission of AML. To the best of our knowledge we here report on the latest AML relapse after allo‐BSCT experiencing SR.